Impact of expected value on neural activity in rat substantia nigra pars reticulata - Bryden, Daniel W. (2011)
The substantia nigra pars reticulata (SNr) is thought to serve as the output of the basal ganglia, whereby associative information from striatum influences behavior via disinhibition of downstream motor areas to motivate behavior. Unfortunately, few studies have examined activity in SNr in rats making decisions based on the value of predicted reward similar to those conducted in primates. To fill this void, we recorded from single neurons in SNr while rats performed a choice task in which different odor cues indicated what reward was available on the left or on the right. The value of reward associated with a left or rightward movement was manipulated by varying the size of and delay to reward in separate blocks of trials. Rats were faster or slower depending on whether the expected reward value was high or low, respectively. The number of neurons that increased firing during performance of the task outnumbered those that decreased firing. Both increases and decreases were modulated by expected value and response direction. Neurons that fired more or less strongly for larger reward tended to fire more or less strongly for immediate reward, reflecting their common motivational output. Finally, value selectivity was present prior to presentation of cues indicating the nature of the upcoming behavioral response for both increasing- and decreasing-type neurons, reflecting the internal bias or preparatory set of the rat. These results emphasize the importance of increasing-type neurons on behavioral output when animals are making decisions based on predicted reward value.